Notes on structural distinctions in Malay dialects - Ogloblin, Alexander K. (UI Scholars Hub, 2018)
Some features of phonology, morphophonemics, and morphology are offered, which seem to be useful for classifying Malay dialects on structural basis. Dialectal differences with Standard Malay are illustrated on minor samples of Johor and Kelantan dialects recorded during author’s stay in Malaysia several decades ago.